THE NEED TO INVESTIGATE STUDENT PERFORMANCE THROUGH DIAGNOSTIC TESTS IN HIGHER EDUCATION - Roziah Keria; Noorsuhada Md Nor; Soffian Noor Mat Saliah, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Early identification of student performance in civil engineering plays a crucial role in improving academic outcomes. Diagnostic tests are practical tools in this process. This study examined the performance of 38 students in Course SM through a diagnostic test administered in the first week. Various statistical methods, such as minimum, mean, standard deviation, t-test, and Pearson Correlation, were utilised to analyse the scores of male and female students separately. The results indicated that male students initially outperform female students in the diagnostic test. However, by the end of the semester, female students demonstrate a remarkable average percentage improvement of 129%, compared to 59% increase for male students. These results suggest that female students show a more significant enhancement in their performance throughout the course. The findings underscore the importance of early diagnosis of student performance, offering valuable insights into individual strengths and areas needing development. By understanding these aspects, educators can adapt their teaching approaches to enhance overall academic success in civil engineering programs.